字典翻译 问答 初中 数学 【初一数学已知(y-z)^2+(z-x)^2+(x-y)^2=(y+z-2x)^2+(x+z-2y)^2+(x+y-2z)^2,求证x=y=z】
问题标题:
【初一数学已知(y-z)^2+(z-x)^2+(x-y)^2=(y+z-2x)^2+(x+z-2y)^2+(x+y-2z)^2,求证x=y=z】
问题描述:

初一数学

已知(y-z)^2+(z-x)^2+(x-y)^2=(y+z-2x)^2+(x+z-2y)^2+(x+y-2z)^2,求证x=y=z

姜广田回答:
  证明   设a=y-z,b=x-y,c=z-x,显然a+b+c=0   则a²+b²+c²=(c-b)²+(b-a)²+(a-c)²   =>a²+b²+c²=2ab+2bc+2ca   (a+b+c)²=0   a²+b²+c²+2ab+2bc+2ca=0   则2(a²+b²+c²)=0   故a=b=c=0   则x=y=z
点击显示
数学推荐
热门数学推荐
  • 语文
  • 数学
  • 英语
  • 政治
  • 地理
  • 历史
  • 化学
  • 生物
  • 物理
  • 音乐
  • 体育
  • 美术